Microstructure and mechanical properties of friction welded AISI 1040/AISI 304L steels before and after electrochemical corrosion - Sarsilmaz, Furkan; Kirik, Ihsan; Ozdemir, Niyazi (Carl Hanser Verlag, 2018)
The aim of the present study is to investigate the effect of welding parameters both on the electrochemical corrosion behavior and tensile strength of pre- and post-electrochemical corrosion of friction welded dissimilar steels. The microstructural changes of AISI 1040/AISI 304L friction welded couples and also parent materials were analyzed by using scanning electron microscopy. The electrochemical behaviors of AISI1040/AISI304L joints were comparatively investigated by potentio-dynamic polarization curve test and by electrochemical impedance spectra. Moreover, tensile strength experiments were carried out determining the behavior of friction welded joints of pre-and post-electrochemical corrosion and results indicated that the maximum tensile test value of the dissimilar welded pre-electrochemical corrosion was higher than those of post-electrochemical corrosion and was also very close to AISI 1040 parent material value.
Keywords: AISI1040; AISI304L; friction welding; electrochemical corrosion; mechanical behavior